DIVERSITY AND ABUNDANCE OF PHYTOPLANKTON AND ZOOPLANKTON IN FRESHWATER ECOSYSTEMS OF RI-BHOI AND EAST KHASI HILLS DISTRICTS, MEGHALAYA - KYNTIEWLANG MARY KHARBYNGAR,; JOHN ALKIN KHONGJOH,; IADALANGKI BAMON,; PYNSHANLANG LASO,; MANDY MARY KHARBYNGAR,; ELVIS KHONGMAWLOH, (The Bioscan, 2024)
Plankton was found to play essential roles in nutrient cycling, energy transfer, and maintaining ecosystem stability. This study, conducted during 2023–2024, examined the diversity of freshwater phytoplankton and zooplankton in two locations in Meghalaya: Ri-Bhoi District (Umsning) and Laitsohpliah Tyngammasi in the East Khasi Hills. A rich variety of plankton, including green algae, blue-green algae, diatoms, desmids, protozoa, rotifers, and crustaceans, was documented across these sites. While some species exhibited regional specificity, many were widely distributed, highlighting their adaptability and ecological significance. The findings underscore the importance of identifying and conserving freshwater plankton due to their critical contributions to aquatic food webs and ecosystem functions, providing valuable insights for the sustainable management of freshwater habitats.